Experimental study on Young's modulus E of a polymer composite reinforced by nano titanium dioxide particles - Duc, Nguyen Dinh; Minh, Dinh Khac (Vietnam Journal of Mechanics, 2012)
There are many formulas proposed by different authors in order to determine elastic modules for composite filler particles. This article aims to present the experiment's results and to review some formulas for determining Young's modulus of elasticity E of the polyester filler titanium dioxide particles composite. The results showed that there was a relatively good fit between theory and practice of some formulas.